Rheological Behaviour of HTPB-based Composite Propellant: Effect ofTemperature and Pot Life on Casting Rate - Mahanta, A.K.; Dharmsaktu, Ila; Pattnayak, P.K. (Defence Science Journal, 2007)
To study the rheological properties and the flow behaviour of HTPB based compositepropellant, a typical mix was carried out with 86 per cent solid loading and toluene diisocynate(TDI) as curator. Viscosity of the propellant slurry was measured at different shear rates overa range of temperature from 40 ºC to 60 ºC at various time intervals up to five hours from endof mix. The data are analysed using power law fluid equation to determine the viscosity index(K) and pseudoplasticity index (m). From these, optimum casting temperature and useful pot lifewas evaluated. Casting rates at different temperatures were determined by Haegen-Poisseuilleequation modified for non-Newtonian fluid flow, using K and m.